Examining the pelleting system - Fairchild, Fred J. (My University, 2015)
This is the second article in a two-part series on the pelleting system. The first article, published in the February issue of World Grain, covered the system from the mash supply bins through the pellet cooler. This article will cover the rest of the system. After cooling, the pellets may be crumbled, screened, coated with additional liquid or sent directly to bulk or bagging bins.
Keywords: Feed processing; Pelleting; Pellet crumbling; Screening